Efficiency of dynamic frequency selection based coexistence mechanisms for TV white space enabled cognitive wireless access points - Sum, Chin-Sean (2013)
We investigate the efficiency of dynamic frequency selection (DFS) in mitigating interference among neighboring low-power cognitive wireless portable networks operating in the TV white space. We derive an interference model to predict the range and level of interference generated in the TV bands by portable low-height antenna cognitive wireless access points in suburban and urban areas. Based on the aforementioned model, we provide an analysis of the spectral availability for either the scenarios where DFS coexistence is employed or not. The steps of our analysis are introduced in a tutorial fashion, and a coexistence case study of TVWS enabled low-power cognitive wireless portable APs in Japan is presented. Our analysis demonstrates the intrinsic relationship SA holds with the TVWS channel set as well as statistical information (e.g., household density of wards and cities, Internet penetration, and white space radio AP market penetration).